2020
DOI: 10.1371/journal.pone.0235803
|View full text |Cite
|
Sign up to set email alerts
|

Toll like Receptor signalling by Prevotella histicola activates alternative NF-κB signalling in Cystic Fibrosis bronchial epithelial cells compared to P. aeruginosa

Abstract: Cystic Fibrosis (CF), caused by mutations affecting the CFTR gene, is characterised by viscid secretions in multiple organ systems. CF airways contain thick mucus, creating a gradient of hypoxia, which promotes the establishment of polymicrobial infection. Such inflammation predisposes to further infection, a self-perpetuating cycle in mediated by NF-κB. Anaerobic Gram-negative Prevotella spp. are found in sputum from healthy volunteers and CF patients and in CF lungs correlate with reduced levels of inflammat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…However, their precise role in airway disease is poorly understood due to conflicting reports about their beneficial vs. pathogenic potential. For instance, P. melaninogenica, P. salivae and P. nanceiensis may inhibit non-typeable Haemophilus influenzae-induced pro-inflammatory cytokine production by lung dendritic cells [53], increased P. melaninogenica prevalence in CF airways has been associated with improved lung function [15], and P. histicola can mute pro-inflammatory pathways triggered by P. aeruginosa in CF airways [57].…”
Section: Resultsmentioning
confidence: 99%
“…However, their precise role in airway disease is poorly understood due to conflicting reports about their beneficial vs. pathogenic potential. For instance, P. melaninogenica, P. salivae and P. nanceiensis may inhibit non-typeable Haemophilus influenzae-induced pro-inflammatory cytokine production by lung dendritic cells [53], increased P. melaninogenica prevalence in CF airways has been associated with improved lung function [15], and P. histicola can mute pro-inflammatory pathways triggered by P. aeruginosa in CF airways [57].…”
Section: Resultsmentioning
confidence: 99%
“…However, their precise role in airway disease is poorly understood due to conflicting reports about their beneficial vs. pathogenic potential. For instance, P. melaninogenica, P. salivae , and P. nanceiensis may inhibit non-typeable Haemophilus influenzae -induced pro-inflammatory cytokine production by lung dendritic cells 52 , increased P. melaninogenica prevalence in CF airways has been associated with improved lung function 15 , and P. histicola can mute pro-inflammatory pathways triggered by P. aeruginosa in CF airways 55 . In contrast, P. melaninogenica produced the greatest variety of short-chain fatty acids (associated with inflammation) amongst five tested anaerobes 18 , and P. denticola shares similarities in its lipid A moieties to P. intermedia (a known pathogenic species), pointing towards pro-inflammatory traits 56 .…”
Section: Resultsmentioning
confidence: 99%
“…It is known that airway epithelial cells have innate sensor functions and may detect microbial signals (Weitnauer et al, 2016). It was shown in a recent report that Rothia mucilaginosa could inhibit host NF-kB pathway activation in a human lung epithelial cell line (Rigauts et al, 2021), and another commensal Prevotella histicola was reported to be able to induce alternative NF-kB activation in CF bronchial epithelial cells (Bertelsen et al, 2020). Earlier work from us has shown that airway epithelial cells adjust their expression pattern of innate immune receptors with less TLR2 and CD36 being expressed, resulting in low reactivity towards microbes that preferentially activate through TLR1/2 or TLR2/6.…”
Section: Discussionmentioning
confidence: 99%